Crafting wellness: exploring the effectiveness of a single-item mental health measure for young children and their mothers - Sıddika Songül Yalçın; Özlem Tezol; Meryem Erat Nergiz; Bülent Güneş; Adnan Barutçu; Emel Kabakoğlu Ünsür; Nalan Karabayır; Zeynep Yılmaz Öztorun; Habip Almiş (Annals of General Psychiatry)
Abstract Background Recognizing the integral role of parental emotional and behavioral health in shaping a supportive family environment crucial for a child’s emotional well-being, a practical tool for evaluating mental health in both preschool children and their mothers are necessary. In this methodological study conducted across eight provinces in Turkey, we aimed to develop and assess the psychometric properties of a single-item mental health measure for physically healthy children aged 2–5 years and their mothers. Method The study included 411 child-mother pairs recruited from tertiary care hospitals, with subjects selected from well-child departments. Various psychometric assessments were employed, including the Strengths and Difficulties Questionnaire (SDQ) for children, Depression, Anxiety, and Stress Scale (DASS-21), Patient Health Questionnaire-4 (PHQ-4) for mothers, and single-item measures for both child and maternal mental health [mother-reported mental health of child (MRCMH) and self-reported mental health of mother (SRMH)]. Data were collected at two time points: baseline evaluation for validity testing and test-retest evaluation at the 3rd week. Results The MRCMH indicated excellent validity, with sensitivity and specificity for detecting borderline and abnormal mental health difficulties in children at 90%, 100%, and 83%, respectively. The SRMH revealed sensitivity and specificity of 62% and 78% for identifying maternal depression, 57% and 76% for anxiety, 63% and 76% for stress, and 54% and 87% for psychological distress, respectively. Construct validity analyses revealed significant correlations between MRCMH and SDQ scores, as well as between SRMH and DASS-21 and PHQ-4 scores. Test-retest reliability, assessed through intraclass correlation coefficients, indicated varying agreement levels, with the highest agreement observed for SDQ total difficulties and the lowest for SRMH. Further exploration of the measures’ sensitivity and specificity revealed noteworthy accuracy in detecting child mental difficulties and maternal psychological distress. Correlational analyses between baseline and 3-week scores highlighted the stability of MRCMH and SRMH over time. Conclusion This research contributes valuable insights into the psychometric properties of single-item measures for child and maternal mental health, offering a potential tool for clinicians and researchers. The outcomes can inform public health strategies and interventions aimed at promoting positive mental health outcomes in preschool children and their mothers.